2002
DOI: 10.1046/j.0007-1323.2001.02054.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of long-term outcome after resection of hepatitis C virus-related hepatocellular carcinoma by postoperative interferon therapy

Abstract: Postoperative interferon therapy seems to improve the outcome after resection of HCV-related HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
148
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(154 citation statements)
references
References 19 publications
6
148
0
Order By: Relevance
“…8,12,[30][31][32][33][34][35] Of the 8 studies, 3 were from the same research center 30,31,34 ; 1 of the 3, which did not provide the essential data, was excluded 34 ; in the remaining 2 studies that were by the same first author, the patients were the same, and some of the related data were also overlapping 30,31 ; moreover, each of the 2 studies 30,31 offered only part of the data that we wanted to extract, so to obtain full information, we combined the 2 studies and considered them as one. 30,31 Thus, finally 6 studies including 600 patients were included in this meta-analysis. 8,12,[30][31][32][33]35 Two studies were performed in China, 8,35 2 in Japan, 30-32 1 in 12 HCC was treated with resection before use of IFN-a in 4 studies, 8,12,30,31,35 and treated with ablation in 2 studies.…”
Section: Selection and Characteristics Of The Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…8,12,[30][31][32][33][34][35] Of the 8 studies, 3 were from the same research center 30,31,34 ; 1 of the 3, which did not provide the essential data, was excluded 34 ; in the remaining 2 studies that were by the same first author, the patients were the same, and some of the related data were also overlapping 30,31 ; moreover, each of the 2 studies 30,31 offered only part of the data that we wanted to extract, so to obtain full information, we combined the 2 studies and considered them as one. 30,31 Thus, finally 6 studies including 600 patients were included in this meta-analysis. 8,12,[30][31][32][33]35 Two studies were performed in China, 8,35 2 in Japan, 30-32 1 in 12 HCC was treated with resection before use of IFN-a in 4 studies, 8,12,30,31,35 and treated with ablation in 2 studies.…”
Section: Selection and Characteristics Of The Trialsmentioning
confidence: 99%
“…8,12,[30][31][32][33]35 Two studies were performed in China, 8,35 2 in Japan, 30-32 1 in 12 HCC was treated with resection before use of IFN-a in 4 studies, 8,12,30,31,35 and treated with ablation in 2 studies. 32,33 Resection as initial treatment for HCC was reported in 3 studies, 8,30,31,35 and resection with pre-resection ablation reported in 1 study. 12 In the 6 RCTs, all of the patients with HCC, proved mostly by pathology or histology, underwent therapies with complete resection or ablation; and IFN-a was used as adjuvant therapy initially after resection or ablation of HCC in each study.…”
Section: Selection and Characteristics Of The Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first RCT of IFN adjuvant therapy appeared in 2000 [45], four other RCTs have been published [46][47][48][49]. Studies have indicated that IFN decreases the rate of HCC recurrence, and the results of our meta-analysis, totalling 196 patients, consistently show a statistically significant benefit on HCC recurrence.…”
Section: Interferonmentioning
confidence: 56%
“…Therefore, all these data underscore, from a practical point of view, the need for adjuvant therapy (tertiary prevention) in the effort to prolong survival and reduce recurrence rates. In the past, different anticancer agents have been evaluated for tertiary prevention of HCC recurrence, including retinoids [42], intra-arterial I-131 [43], adoptive immunotherapy [44], and finally IFN [45][46][47][48][49]. Recently, sorafenib, an oral multi-kinase inhibitor targeting both tumor cells and the tumor vasculature is being evaluated in the setting of tertiary chemoprevention.…”
Section: Tertiary Chemopreventionmentioning
confidence: 99%